Scattering near‐field optical microscopy on metallic and semiconducting carbon nanotube bundles in the infrared. Issue 12 (23rd June 2016) - Németh, Gergely; Datz, Dániel; Tóháti, Hajnalka M.; Pekker, Áron; Kamarás, Katalin
Abstract: We demonstrate that scattering‐type near‐field optical microscopy (s‐SNOM) at infrared frequencies can be effectively used to distinguish between carbon nanotube (CNT) bundles based on their electrical properties. Samples from separated metallic and semiconductor nanotubes and their mixtures were investigated using infrared lasers under near‐field conditions. In this frequency range, the difference in the free‐carrier concentration between metallic and semiconducting tubes is expected to influence the properties of the scattered light. The remarkable difference in the optical phase images proves that this is indeed the case: the metallic and semiconducting bundles are unambiguously identifiable in the sample, even in case of 5 nm diameter bundles. The measurements agree qualitatively with our calculations based on the extended finite dipole model using the known optical functions of the constituting nanotubes.